Lunar Agricultural Module Ground Test Demonstrator - an international approach for realizing plant-based bio-regenerative life-support - Maiwald, Volker; Neufeld, Charmaine Claire; Franke, Michel Fabien; Schubert, Daniel (2024)
Long-term human lunar exploration requires advancement of life support systems. Bio-regenerative life support systems (BLSS) have been shown to have a reduced equivalent mass for such long-term missions compared to more traditional methods, e.g., physical-chemical life support, which reduces mission costs and effort in general. Currently, no such (near) closed-loop systems exist and several challenges for their realization are still present, such as understanding of e.g., scaling of the system, interaction of technical and biological components, interaction and dependency of technical elements, and the microbiome. Beginning with a prototype-test in Antarctica, the German Aerospace Center (DLR) has joined an international effort, comprising the Canadian Space Agency (CSA) and several subcontractors, in now creating a Ground Test Demonstrator (GTD) capable of addressing the many unknowns of designing, developing and operating a Lunar Agriculture Module (LAM). This paper aims to present the current updated status of the design and project and informs about the international effort behind it, highlighting the importance of the project. We present a system overview and inform about how the system will be able to address open issues currently associated with BLSS as well as a roadmap of the LAM-GTD usage and how it will eventually lead to the operation of an actual agricultural module on the lunar surface.